Dust accumulation and loess formation under the oceanic semiarid climate of Tenerife, Canary Islands - Kis, Éva; Schweitzer, Ferenc (Hungarian Geographical Bulletin, 2010)
Sediments formed by mixing dust of Saharan origin with local weathered pyroclastic rocks were investigated using granulometric analyses for environmental reconstruction. For this purpose traditional sedimentological parameters were applied together with indices such as FG (fineness grade) and Kd (degree of weathering). It could be established that surface deposits are loess or loess-like sediments reworked by colluvial processes. It was also concluded that soils formed on alkalic basalt lava are semipedolites i.e. sediments that have undergone pedogenesis of limited extent, whereas on the phonolite genuine paleosols formed. The stratification of sediments show half-year variation instead of annual one due to the alternating dry and wet seasons (parent material being transported by north-eastern and Sahara trade winds). With the exception of the soil developed on the phonolite lava all the deposits studied are younger than 1 Ma.